LncRNA FOXD2-AS1 Functions as a Competing Endogenous RNA to Regulate TERT Expression by Sponging miR-7-5p in Thyroid Cancer - Liu, Xiaoli; Fu, Qingfeng; Li, Shijie; Liang, Nan; Li, Fang; Li, Changlin; Sui, Chengqiu; Dionigi, Gianlorenzo; Sun, Hui (Frontiers in Endocrinology, 2019)
Long non-coding RNA FOXD2 Adjacent Opposite Strand RNA 1 (FOXD2-AS1) has been widely reported to be implicated in the progression and recurrence of several cancers. The clinical significance and functional role of FOXD2-AS1 in thyroid carcinoma remain unknown. FOXD2-AS1 expression was evaluated by analyzing thyroid cancer RNA sequencing dataset from The Cancer Genome Atlas (TCGA). In vitro and in vivo assays were performed to assess the biological roles of FOXD2-AS1 in thyroid cancer cells. Western blot, luciferase, immunoprecipitation (IP) and RNA immunoprecipitation (RIP) assays were used to identify the underlying miRNA and mRNA target mediating the biological roles of FOXD2-AS1 in thyroid cancer cells. FOXD2-AS1 was upregulated in thyroid carcinoma tissues and cells. High expression of FOXD2-AS1 significantly correlated with clinical stage, recurrence of thyroid carcinoma. Silencing FOXD2-AS1 inhibited cancer stem cell-like phenotypes and attenuates the anoikis resistance in vitro. Downregulating FOXD2-AS1 represses the tumorigenesis of thyroid carcinoma cells in vivo. FOXD2-AS1 acts as a competitive endogenous RNA (ceRNA) for miR-7-5p, up-regulating the expression of telomerase reverse transcriptase (TERT), which further promotes the cancer stem cells features and anoikis resistance in thyroid cancer cells. Our findings indicate that FOXD2-AS1 functions as an oncogenic regulator in the development of thyroid cancer, contributing to early recurrence of thyroid cancer.